KNOWING THE JAPANESE CULTURE: THE ART OF FOLDING CLOTH "FUROSHIKI" - Susanti Aror; Sherly F Lensun (JELLT (Journal of English Language and Literature Teaching), 2022)
: This scientific paper examines furoshiki. Furoshiki is a culture of folding fabrics to wrap things. The purpose of this study is to find out the meaning of the furoshiki philosophy for Japanese society and to find out the forms of furoshiki. The method used in this study is a descriptive research method, with literature study techniques for data collection. The data processing technique in this study is collected from existing sources, grouped, then analyzed, and used as the content of the study. Furoshiki can be used to wrap a wide variety of objects with different shapes such as flat objects and round-shaped objects, can be made into bags, and can also be used to decorate rooms. The meaning of the furoshiki philosophy for Japanese society is found in the colors and patterns of the furoshiki. Japanese society believes that the patterns present on the fabric can bring benefits to the recipient. Based on the results of this study, it is hoped that people will have awareness to start reducing the use of plastic for daily needs so as to reduce environmental pollution.